2021
DOI: 10.4314/ahs.v21i3.12
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to oral HIV pre-exposure prophylaxis among female sex workers in Kampala, Uganda

Abstract: Introduction: In Kampala Uganda, female sex workers (FSWs) have high HIV prevalence (33%). Oral PrEP is a novel HIV prevention intervention that offers hope to decrease HIV incidence in key populations especially among FSWs. Studies have shown that with poor adherence, oral PrEP has no efficacy, and therefore adherence to PrEP is critical among FSWs to maximize HIV prevention. However, implementation data on adherence to PrEP among FSWs is limited so this study sought to assess adherence to PrEP. Specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Our study found that the overall PrEP adherence among FSWs was 48.3%, which was lower than that observed in other countries. [18,22] The present study found that living with family, pill packaging, and perception of PrEP were associated with adherence.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Our study found that the overall PrEP adherence among FSWs was 48.3%, which was lower than that observed in other countries. [18,22] The present study found that living with family, pill packaging, and perception of PrEP were associated with adherence.…”
Section: Discussionmentioning
confidence: 50%
“…The sample size of FSWs included in the present study to determine adherence to oral HIV PrEP was calculated based on the level of adherence to oral HIV PrEP among FSWs in Kampala, Uganda, which was 71%. [18] The sample size was estimated using the Kish-Leslie formula (1965) as follows: [19] Sample Size…”
Section: Sample Size Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 Furthermore, interventions such as PrEP adherence support groups that meet physically or online via WhatsApp have been set up for female sex workers in Uganda to improve adherence for those on PrEP to offer social support to each other. 30 However, our findings also highlight the need to address the economic and social barriers that may prevent female sex workers from accessing HIV prevention services. A recent study in Mexico identified financial constraints and social stigma as some of the barriers to PrEP use among female sex workers.…”
Section: Discussionmentioning
confidence: 78%
“…in the study showed that high LTFU to PrEP has been found among PrEP user who didn’t use contraception methods. We can therefore see a link between lost follow up and contraceptive use and therefore intensified contraceptive counseling and screening before PrEP initiation and during PrEP use may improve PrEP adherence among users (25).…”
Section: Discussionmentioning
confidence: 99%